Condylar displacement on three different biotypological facial groups - Maria João Ponces (2012)
This work intended to investigate centric slide (CS) on different facial skeletal groups. With this aim in mind, three different groups hyperdivergent, hipodivergent and an intermediate one were studied and compared. The tests performed allowed to identify a statistically more significant vertical displacement in hyperdivergent group while the sagittal displacement was more pronounced in hypodivergent group with a relative level of significance. Regardless of the facial type, vertical displacements were more marked than sagittal. The results allow concluding that CS is independent of facial types and that in the special case of hyperdivergent it should be carefully evaluated and considered in the study of clinical cases.